Application of Hybrid Transient Thermal Tensioning/Trailing Active Cooling Treatment for Minimizing Distortion, Residual Stress, and Fatigue Crack Growth Rate of Friction Stir Welding Joints - Ilman, Mochammad Noer (Springer, 2022)
n the present study, a hybrid in-process thermal treatment consisting of transient thermal tensioning (TTT) and trailing active cooling (TAC) has been applied to friction stir welding (FSW) of AA5083-H116 aluminum alloy plates with the main objective of improving fatigue crack growth performance of the weld joints. The TTT treatment was conducted during welding by placing two symmetrical secondary heat sources at both sides of the weldline ahead the tool at a heating temperature of 200°C combined with TAC treatment which employed quenching behind the tool. It was found that the hybrid TTT/TAC treatment showed excellent weld fatigue crack growth rate. In addition, the hybrid TTT/TAC treatment also showed better efficacy for minimizing distortion than single TTT or TAC treatment with the welding distortion reduction by the hybrid TTT/TAC treatment of 48.3 ±3.7% compared to as welded FSW joint. The beneficial effects of the hybrid TTT/TAC treatment seemed to be associated with temperature field modification which generated stronger thermal tensioning against compressive shrinkage stress in the weld region resulting in lower distortion and residual stress. This condition together with microstructural changes under hybrid TTT/TAC treatment could reduce fatigue crack growth rate of the FSW joints.